A plant-wide energy model for wastewater treatment plants: application to anaerobic membrane bioreactor technology. Issue 18 (16th September 2016) - Pretel, R.; Robles, A.; Ruano, M.V.; Seco, A.; Ferrer, J.
ABSTRACT: The aim of this study is to propose a detailed and comprehensive plant-wide model for assessing the energy demand of different wastewater treatment systems (beyond the traditional activated sludge) in both steady- and unsteady-state conditions. The proposed model makes it possible to calculate power and heat requirements ( W and Q, respectively), and to recover both power and heat from methane and hydrogen capture. In order to account for the effect of biological processes on heat requirements, the model has been coupled to the extended version of the BNRM2 plant-wide mathematical model, which is implemented in DESSAS simulation software. Two case studies have been evaluated to assess the model's performance: (1) modelling the energy demand of two urban wastewater treatment plants based on conventional activated sludge and submerged anaerobic membrane bioreactor (AnMBR) technologies in steady-state conditions and (2) modelling the dynamics of reactor temperature and heat requirements in an AnMBR plant in unsteady-state conditions. The results indicate that the proposed model can be used to assess the energy performance of different wastewater treatment processes and would thus be useful, for example, WWTP design or upgrading or the development of new control strategies for energy savings.